Renungan Ekoteologis KH. KPP. Noer Nasroh Hadiningrat di Pesantren Walisongo Tuban - Fikri Mahzumi (Islamica: Jurnal Studi Keislaman, 2018)
This article is an attempt to describe the theological paradigm of environment existing in Pesantren Walisongo Tuban. From an academic perspective, this paradigm is often regarded as eco-theology. This discourse has been widely discussed by many experts and activists of environment from different countries as new attempts to cope with global crisis faced by human being. KH KPP Noer Nasroh Hadiningrat who is far way from the discourse of eco-theology has naurallybuilt a paradigm related to the issue of environment based on his reflection on Islamic values and traditions. Forest which becomes his dominant environment where his pesantren is located has led him to cosmic awareness of the importance of conserving the mandat of God to human being. This awareness manifests in what is called â€œthe words of forestâ€ (kalam rimba) transferred to students and society around pesantren. In addition, Kiai Noer as the key actor also get involved in practical activities such as establishing vocational school of forestry to establish a continous transformation and implication for the conserva-tion of forest with its ecosystem, particularly in Indonesia.